2020
DOI: 10.1111/1742-6723.13467
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing in patients who presented to the emergency department with dog bites: A descriptive review of current practice

Abstract: Objective: To describe the current practice of prophylactic antibiotic prescribing for patients presenting to the Emergency Department (ED) with a dog bite, and compare management against existing guidelines. Method: We performed a descriptive retrospective study on all consecutive patients who presented to one tertiary teaching hospital and one regional district hospital in Southeast Queensland between the 1st of July 2017 and the 30th of June 2018 with a presentation of a dog bite. Data on demographics and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
3
4
0
Order By: Relevance
“…The median age of the bite patients was similar to that found in other studies (28.0-36.0 years; Baxter et al, 2020;Jaindl et al, 2016;Nkomo et al, 2020;Pfortmueller et al, 2013), with a predominance of men, as identified in the majority of previous studies (51.8%-55.0%; Baxter et al, 2020;Jaindl et al, 2012;Ngugi et al, 2018;Nkomo et al, 2020;Pfortmueller et al, 2013;Wangoda et al, 2019;Williams et al, 2021); however, in other reports, a higher proportion of women has been described (50.6%-62.0%; Birdsey et al, 2016;Jaindl et al, 2016;Morzycki et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The median age of the bite patients was similar to that found in other studies (28.0-36.0 years; Baxter et al, 2020;Jaindl et al, 2016;Nkomo et al, 2020;Pfortmueller et al, 2013), with a predominance of men, as identified in the majority of previous studies (51.8%-55.0%; Baxter et al, 2020;Jaindl et al, 2012;Ngugi et al, 2018;Nkomo et al, 2020;Pfortmueller et al, 2013;Wangoda et al, 2019;Williams et al, 2021); however, in other reports, a higher proportion of women has been described (50.6%-62.0%; Birdsey et al, 2016;Jaindl et al, 2016;Morzycki et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, more than two-thirds of patients received a prescription for an antibiotic for prophylactic purposes, a finding similar to that documented in Switzerland (70.4%; Pfortmueller et al, 2013) and Canada (67.0%; Morzycki et al, 2019) but different from that described in Australia, where the proportion of antibiotic prescriptions was even higher (86.6%; Baxter et al, 2020); in countries such as the USA, Austria and South Africa, the antibiotic prescription rates were lower (13.9%-45.1%; Jaindl et al, 2012Jaindl et al, , 2016Nkomo et al, 2020;Tabaka et al, 2015). Additionally, 4.3% of the patients already had a bacterial superinfection at the time seeking medical care, a finding that is consistent with what was previously published in North America (4.4%-5.2%; McGuire et al, 2018;Tabaka et al, 2015) but lower than that found in Austria (10.7%-19.0%; Jaindl et al, 2012;Jaindl et al, 2016).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…AP is only recommended for selected patients (See Table 1 for suggested indications as well as relevant references [11,21,22]). However, AP is used in a significant proportion of patients beyond the recommended indications [23].…”
Section: Overuse Of Antibiotic Prophylaxis In Bite Woundsmentioning
confidence: 99%